Encyclopedia of post colonial literatures in english [2 volumes set] - Benson, Eugene [ed.]; Conolly, L. W. [ed.] (London Routledge, 1994)
a literary and organizational achievement that will support cirricular trends at most campuses...Cross references and a full, text-generated index are a user's delight.."-Choice, February 1995 "With the growing multicultural emphasis on literature, this work is a welcome and needed source. Highly recommended for all undergraduate colleges."-Library Journal, October 15, 1994 ..."This major work should find a place in academic and research library collections...."-American Reference Books Annual, 1995 ..."a comprehensive, reliable and up-to-date compendium...The "EPCLE is certain to be an invaluable and standard reference resource for at least the next decade in the field of post-colonial literary studies."-World Literature Today, Winter 1996
Keywords: Commonwealth literature (English); Decolonization in literature; Imperialism in literature